Comparison of modafinil and pitolisant in narcolepsy: a non-inferiority metaanalytical approach - Philippe Lehert; Cassandra Szoeke (BioExcel Publishing Ltd, 2020)
Aim: To assess the non-inferiority of pitolisant, a new compound for the relief of excessive daytime sleepiness (EDS) and cataplexy in narcolepsy, compared with modafinil. Methods: Randomized controlled trials (RCTs) in narcolepsy were searched systematically. Network meta-analysis (NMA) compared the efficacy and safety of pitolisant and modafinil. The main endpoints are Epworth Sleepiness Scale (ESS), Maintenance of Wakefulness Test (MWT), the number of cataplexies, and overall safety. Results: Of 312 articles after removing duplicates, 10 RCTs were eligible for NMA. For ESS, a non-significant superior beneficial decrease (−0.69, [−2.18, 0.79]) showed non-inferiority of pitolisant (non-inferiority margin [NIM]=1, p=0.015). An MWT beneficial increase (2.12 minutes [−0.95, 5.19]; p=0.18) showed non-inferiority of pitolisant (NIM=−1). For cataplexy, the mean beneficial effect of pitolisant was significant, providing evidence of pitolisant superiority in addition to non-inferiority. The risk ratio (RR) of treatment-suspected adverse events for pitolisant/ modafinil was 0.86 [0.44, 1.24] favoring pitolisant, confirming non-inferiority considering a safety margin of RR=1.25 (tolerance of 25%). Conclusions: Pitolisant is non-inferior to modafinil in relieving EDS, but superior to modafinil in reducing cataplexy, outranking modafinil in narcolepsy type-1 patients. Despite a slight superiority of pitolisant in EDS relief, both drugs perform equally in narcolepsy type-2 patients.